Comparison of the nuclear power industry in Czech Republic and France - Loiseau, Jean-Camille; Šauer, Petr; Dvořák, Antonín; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2010)
This paper studies the nuclear technology and evaluates the most likely technical developments to come until 2030. It examines the features of Czech and French nuclear programs, compares the structures of nuclear sectors and estimates the advantages & drawbacks of further developments in both countries. The paper assesses if certain developments of the nuclear sector in one country can be used in the other country and vice-versa. Finally, proposes a set of recommendations for both countries regarding the development of their nuclear program.
Vedoucí práce: Petr Šauer
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2010
Rok obhajoby 2010
Keywords: international Business - Central European Business Realities [obor dipl. práce]; diplomové práce; master's theses